Role of serum biomarkers in prediction and prognosis of Chagas disease - Khan, Adnan; Justus Liebig University Giessen (My University, 2015)
Chagas disease (CD), caused by the hemoflagellate protozoan, Trypanosoma cruzi, is endemic in most countries of South and Central America, where nearly 10 million people are infected with the parasite and another 25 million are at risk of infection. Cardiac involvement is the most frequent and serious manifestation of chronic CD, and typically leads to abnormalities of conduction system, heart failure (HF), thromboembolism, and sudden death. HF is often a late manifestation of chronic CD and is associated with higher mortality than is HF from other causes. Early identification of patients with CD, therefore, would be desirable as early intervention may help improve prognosis. Inflammatory biomarkers can play a vital role in early diagnosis, as inflammation mediated by cytokines plays an important role in pathogenesis and progression of CD, and may be present even in the absence of HF.Keeping in view the inflammatory nature of CD, this study investigated the possible role of 21 different inflammatory cytokines as biomarkers for prediction and prognosis of CD. The plasma concentration of each of these cytokines was measured in a group of patients with CD, and then compared with those measured in patients with dilated cardiomyopathy (DCM) from idiopathic causes, and with control subjects. This study was the first to demonstrate cytokines such as monokine induced by interferon gamma (MIG) and stem cell growth factor beta (SCGF beta) in CD and idiopathic DCM patients with HF. Although plasma levels of cytokines like SCGF beta, hepatocyte growth factor (HGF), cutaneous T-cell attracting chemokine (CTACK), and MIG were significantly increased in CD patients with advanced HF, they were unable to show any predictive or prognostic potency in CD. Multivariate analysis was able to prognosticate a large proportion of CD and DCM patients, but it could not discriminate CD from idiopathic DCM. It is possible that some of the cytokines that were investigated here are only regulated in HF due to specific etiologies such as ischemic HF. Also, cytokines other than the ones that were investigated may play a major role in causing severe inflammation and fibrosis seen in CD.Studies in future should focus on identifying more serum inflammatory biomarkers that could be used as tools for early prediction and prognosis of CD. As CD is associated with poor prognosis, identifying patients at an early stage of the disease may help in providing effective treatment and prevent the development of HF and thus early death.

Die Chagas-Krankheit (CD) ist eine von Trypanosoma cruzi verursachte Protozoeninfektion, die endemisch in den meisten Ländern Süd-und Mittelamerikas auftritt und 10 Millionen Menschen betrifft sowie weitere 25 Millionen Menschen gefährdet. Ein Herzphänotypist ist die häufigste und schwerste Manifestation der chronischen CD und führt meistens zu Störungen des Reizleitungssystems, zu Herzinsuffizienz (HF), Thromboembolien und plötzlichem Tod. Die HF ist oft eine späte Folge der CD und ist mit einer höheren Sterblichkeit verbunden als eine durch andere Ursachen hervorgerufene HF. Die Früherkennung der CD in Patienten wäre daher wünschenswert, da frühe Intervention zur Prognoseverbesserung führen kann. Entzündliche Biomarker können eine entscheidende Rolle bei der frühen Diagnose spielen, da die von Zytokinen vermittelte Entzündung eine wichtige Funktion in der Pathogenese und Progression von CD spielt und auch in Abwesenheit von einer HF vorhanden sein kann.Unter Berücksichtigung der entzündlichen Eigenschaften der CD ist in der vorliegenden Arbeit, die mögliche Rolle von 21 verschiedenen inflammatorischen Zytokinen als Biomarker für die Diagnose und Prognose der CD untersucht worden. Die Plasmakonzentration jedes dieser Zytokine wurde in einer Gruppe von Patienten mit CD gemessen und anschließend mit Werten von Patienten mit dilatativerKardiomyopathie (DCM) aus idiopathischen Gründen sowie mit den Werten von Kontrollpersonen verglichen. Die Studie zeigte zum ersten Mal Zytokine wie monokine induced by interferon gamma (MIG) und Stammzellwachstumsfaktor beta (SCGF Beta) in CD- und idiopathischen DCM-Patienten im Zusammenhang mit HF. Obwohl die Plasmaspiegel von Zytokinen wie SCGF beta, Hepatozyten-Wachstumsfaktor (HGF), kutanem T-Zell-anziehendem Chemokin (CTACK) und MIG in CD-Patienten mit fortgeschrittener HF deutlich erhöht waren, konnte ihre diagnostische oder prädiktive Potenz in der CD nicht nachgewiesen werden. Die Multivariate Analyse konnte nicht zwischen CD-Patienten und idiopathischen DCM-Patienten unterscheiden, obwohl der klinische Verlauf für einen großen Anteil der CD- und DCM-Patienten richtig prognostiziert werden konnte. Es ist möglich, dass einige der hier untersuchten Zytokine nur in spezifischen Ätiologien der HF, wie z.B. der Ischämischen HF, reguliert werden. Außerdem können Zytokine, die von uns nicht untersucht worden sind ebenfalls eine Rolle bei der Entstehung von schweren Entzündungen und Fibrose spielen, die bei CD beobachtet werden.Deshalb besteht die Notwendigkeit, dass sich weitere Studien mit der Identifizierung entzündlicher Serum-Biomarker, als Hilfsmittel für die frühe Diagnose und Prognose von CD, befassen. Da die chronische Chagas-Kardiomyopathie mit einer schlechten Prognose einhergeht, kann die Früherkennung der Krankheit die Einleitung einer wirksamen Behandlung ermöglichen und die Entwicklung einer HF und somit eines frühen Todes verhindern.
Keywords: Chagas disease; dilated cardiomyopathy; heart failure; ddc:610